2015
DOI: 10.3758/s13428-015-0612-1
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of modeling autocorrelation when synthesizing single-case studies using a three-level model

Abstract: Results from single-case studies are being synthesized using three-level models in which repeated observations are nested in participants, which in turn are nested in studies. We examined the performance of these models under conditions in which the errors associated with the repeated observations (the Level-1 errors) were assumed to be first-order autoregressive. Monte Carlo methods were used to examine conditions in which the first-order autoregressive assumption was accurate, conditions in which it represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 40 publications
0
58
0
Order By: Relevance
“…The effect of ignoring autocorrelation and other misspecifications of the level-1 error structure have been examined for MLM analyses for single-case data. Researchers found that ignoring autocorrelation does not bias the fixed effect estimates, but the inferences about the fixed effects can be inaccurate due to the underestimate of the corresponding standard errors, and the estimates of the variance parameters become more biased (Ferron et al, 2009;Owens & Ferron, 2012;Petit-Bois et al,2016). Although MLM allows autocorrelation among level-1 errors to be taken into consideration in single-case data analyses, this approach holds a critical assumption that the level-1 error structure is the same for all cases.…”
Section: Assumption Of Between Case Homogeneity In Level-1 Error Strumentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of ignoring autocorrelation and other misspecifications of the level-1 error structure have been examined for MLM analyses for single-case data. Researchers found that ignoring autocorrelation does not bias the fixed effect estimates, but the inferences about the fixed effects can be inaccurate due to the underestimate of the corresponding standard errors, and the estimates of the variance parameters become more biased (Ferron et al, 2009;Owens & Ferron, 2012;Petit-Bois et al,2016). Although MLM allows autocorrelation among level-1 errors to be taken into consideration in single-case data analyses, this approach holds a critical assumption that the level-1 error structure is the same for all cases.…”
Section: Assumption Of Between Case Homogeneity In Level-1 Error Strumentioning
confidence: 99%
“…Specifically, it is assumed that (a) autocorrelation is the same for all cases and (b) the level-1 error variance is the same for all cases. Previous single-case research using MLM application as well as misspecification research of level-1 error structures has often assumed the autocorrelation and level-1 error variance to be equal for all cases (e.g., Ferron et al, 2010;Petit-Bois et al, 2016;Van den Noortgate & Onghena, 2003).…”
Section: Assumption Of Between Case Homogeneity In Level-1 Error Strumentioning
confidence: 99%
“…Monte Carlo simulations have been used extensively in developing and evaluating methods for analysis of SCD data (e.g., Ferron, Bell, Hess, Rendina-Gobioff, & Hibbard, 2009;Moeyaert, Ugille, Ferron, Beretvas, & Van den Noortgate, 2013;. Simulations are particularly advantageous for studying the robustness of statistical methods because artificial data can be generated based on a model that does not conform to the assumptions of the procedures being studied (e.g., Moeyaert, Ugille, Ferron, Beretvas, & Van den Noortgate, 2016;Petit-Bois, Baek, Van den Noortgate, Beretvas, & Ferron, 2015). Simulations have even been used to examine the performance of analytic methods that are not based on specific distributional assumptions, such as the non-overlap effect sizes for SCDs (e.g., Tarlow, 2017;Pustejovsky, 2018).…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…Apart from the assumption of independence of residuals from different levels, it is also usually assumed that the Level 1 residuals are independent. For that reason, Petit-Bois, Baek, Van den Noortgate, Beretvas, and Ferron (2016) studied the effect of different specifications of the autoregressive error structure for the measurements. They found that in practically all conditions, the treatment effects are unbiased regardless of whether there is misspecification or not, whereas the estimates of the variance components are biased.…”
Section: Summary Of Methodological Evidencementioning
confidence: 99%